Potential Impacts of Liquid-Metal Plasma-Facing Components on Heating and Current Drive Actuators for a Fusion Nuclear Science Facility. (2nd January 2020) - Wallace, G. M.; Kessel, C. E.; Hosea, J.; Majeski, R.; Wilson, J. R.; Rognlien, T.; Waganer, L. M.
Abstract: This paper addresses the potential impact of liquid metal (LM) plasma-facing components (PFCs) for the heating and current drive (H&CD) actuators on the Fusion Nuclear Science Facility (FNSF) fusion reactor. Fulfilling the high neutron fluence mission of the FSNF requires steady-state operation for extremely long pulses (months to years) between maintenance opportunities. The use of LM as a surface material is one strategy for extending the lifetime of the PFCs for long pulse operation in a high heat flux, high neutron flux environment like that of the FNSF. Liquid metal PFCs provide possible pathways forward on many difficult aspects of a fusion reactor; however, the LM PFCs also bring new challenges and unknowns with respect to the H&CD actuators needed to provide steady-state operation. The development of LM-compatible materials for radio-frequency (RF) antennas will be critical, as well as strategies for minimizing contamination of antenna surfaces and the core plasma. Successful deployment of LM PFCs on the FNSF will require operational experience with RF in a LM environment both on test stands and in an integrated toroidal environment.